Super-resolution microscopy of the synaptic active zone - Ehmann, Nadine; Sauer, Markus; Kittel, Robert J. (Frontiers in Cellular Neuroscience, 2015)
Brain function relies on accurate information transfer at chemical synapses. At the presynaptic active zone (AZ) a variety of specialised proteins are assembled to complex architectures, which set the basis for speed, precision and plasticity of synaptic transmission. Calcium (Ca2+) channels are pivotal for the initiation of excitation-secretion coupling and, correspondingly, capture a central position at the AZ. Combining quantitative functional studies with modelling approaches has provided predictions of channel properties, numbers and even positions on the nanometre scale. However, elucidating the nanoscopic organisation of the surrounding protein network requires direct ultrastructural access. Without this information, knowledge of molecular synaptic structure-function relationships remains incomplete. Recently, super-resolution microscopy techniques have begun to enter the neurosciences. These approaches combine high spatial resolution with the molecular specificity of fluorescence microscopy. Here, we discuss how super-resolution microscopy can be used to obtain information on the organisation of AZ proteins.